Kajian Variasi Campuran Wortel (Daucus carota L.) pada Selai Nanas Ditinjau dari Sifat Fisik, Sifat Organoleptik dan Aktivitas Antioksidan - Charisma Rizky Nurtaati; Slamet Iskandar; Idi Setiyobroto (Poltekkes Kemenkes Yogyakarta, 2016)
Background: Today, there are many sought a safe natural antioxidant source, mainly derived from plants. Some fruits and vegetables shown to have high antioxidant activity. Carrot have a lot of antioxidant. During this carrot has not been used optimally. Jam is a semi-solid food made from fruit and sugar. Jam usually made of the crushed fruits. The addition of carrots in jam is expected to add the content of the antioxidant activity and preferred by the consumers so that could become one of the new alternative in an effort to diversify sources of antioxidant for food product. Objective: This study aims to determine the phisycal character, organoleptic character, and the antioxidant activity of the pineapple jam with mix variations of the carrot. Method: The kind of this study is experimental with simple random design. Results: The test data result of the phisycal character, organoleptic character, and the antioxidant activity analyzed by using the descriptive method. The more mix variations of the carrots so the color of the jam became more orange, the taste became langu like the typical of carrot, the smell became langu also like the typical of carrot, and the texture became smoother. The preffered color jam is the mix variations of carrots color 35%. The preffered smell of the jam is the mix variations of carrots 25%. The preffered taste of the jam is mix variations of carrots 35%. The preffered texture of the jam is mix variations of carrots 25%. The more mixture of carrots, the antioxidant activity of pineapple jam became higher. Conclusion: There is a difference in phisycal character, organoleptic character, and the antioxidant activity in pineapple jam with mix variations of carrots. Key words: pineapple jam, carrot, phisycal character, organoleptic character, and the antioxidant activity